Pemanfaatan Ekstrak Bunga Tapak Dara (Catharanthus roseus) Sebagai Insektisida Alami Pembunuh Nyamuk Aedes aegypti - Prasetio, Eko, Drs. Djumadi, M.Kes (2016)
Dengue Hemoragi Fever is growing rapidly infect in Indonesia. Need for ways appropriate countermeasures without the use of harmful chemicals. Vinca flower (Catharanthus roseus) has a chemical content that can be used as a natural insecticide that is geraniol and sitronellol. Geraniol affect the ganglia of the central nervous system of insects that make the mosquitoes paralysis and death results. Sitronellol makes mosquitoes fluid loss continuously. This study aims to describe the killing power of vinca flower extract as a natural insecticide against the mosquito Aedes aegypti. The method used in this research is true experimental research design post test only control group design, using one control treatment that concentrations of 0% and 5 concentrations of extracts of flowers of vinca, ie 60%, 70%, 80%, 90% and 100 %. The results showed that the higher concentration of vinca flower extracts are used, the higher the death of Aedes aegypti and there are differences in the average mortality at various concentrations. Having tested with probit analysis shows the achievement LC50 or means can kill 50% of test mosquito populations,LC50 exist at a concentration of 91.2. While the LC90 and LC99 can not be achieved, which means flower extract of vinca less effective in killing mosquito Aedes aegypti.